Long-Term Effect of Rigid Foot Orthosis in Children Older Than Six Years With Flexible Flat Foot - Youn, Kyo-Jun (Ann Rehabil Med, 2019)
OBJECTIVE: To evaluate the long-term effect of a custom-made rigid foot orthosis (RFO) in children older than 6 years with pes planus (flat foot). METHODS: Medical records of 42 children diagnosed with flexible pes planus who were fitted with RFOs based on the inverted technique and underwent more than four consecutive radiological studies were reviewed. Resting calcaneal stance position (RCSP), anteroposterior talocalcaneal angle, lateral talocalcaneal angle, lateral talometatarsal angle, and calcaneal pitch were initially measured in both feet to evaluate alignment. Followup clinical and radiological evaluations were then performed at 12–18, 24–30, 36–42, and ≥48 months after RFO application. Repeated measures analysis of variance was used to evaluate significant differences. RESULTS: Significant improvements in all radiological indicators and significant progression of RCSP toward the corrective direction were observed after RFO application relative to baseline measurements. CONCLUSION: According to our findings, RFO can induce significant improvements in calcaneus-related radiographic indices and subsequently improve talus-related radiologic indices.